The Missing Shock: The Macroeconomic Impact of British Privatisation - Massimo Florio; Mara Grasseni (Fondazione Eni Enrico Mattei (FEEM), 2004)
The privatisation policy pursued in the UK by Mrs Thatcher's government (1979-1990) and subsequently by Mr Major's government (1990-1997) was the largest experiment in public divestitures among capitalist economies. It had a deep impact on economic policy-making world wide, and was vastly imitated, in Western Europe, in the former planned economies, in a number of less developed countries. In this paper we test the impact of privatisation on macroeconomic performance in the United Kingdom using quarterly data from 1979 to 1999. In the econometric model, we use privatisation proceeds as an explanatory variable and we control for several other variables. Testing for cointegration the results show that there is a long run equilibrium relationship between GDP growth and the variables used in the model. However, in our empirical analysis we find a weak evidence that privatisation generated an aggregate shock on output in the UK. This result is consistent with empirical literature on microeconomic evidence that shows that in the UK ownership change per se had little impact on long term productivity trends.
Keywords: H32; H82; L16; L33; 330; Corporate governance; Privatization; Transition; Ownership structure; Privatisierung; Großbritannien; Wirkungsanalyse